Simplified Formulations for Estimating the Main Frequencies of Ancient Masonry Churches - Lopez, Saulo; D'Amato, Michele; Ramos, Luis; Laterza, Michelangelo; Lourenço, Paulo B. (Frontiers in Built Environment, 2019)
This paper proposes simplified formulations for estimating the main frequencies of ancient masonry churches. The formulations are derived starting from the results of numerical analyses with finite elements models, whose geometric parameters are assigned in accordance with specific relationships established on a set of 50 existing churches. The so-obtained formulations are also compared with the results of a series of experimental dynamic identification tests chosen from literature. Finally, starting from these experimental results, through numerical regressions, formulas for predicting the main frequencies of ancient masonry churches are proposed, too.